Cold quark matter under intense magnetic fields: the role of flavor mixing and vector interactions - Allen, P. G. (2015)
We study the effect of intense magnetic fields on the phase diagram of cold, strongly interacting matter within the Nambu-Jona-Lasinio model. Model extensions that include flavor mixing effects and vector interactions were analyzed, varying all relevant model parameters in acceptable ranges. Charge neutrality and beta equilibrium effects, which are specially relevant to the study of compact stars, were also considered.